2018
DOI: 10.1002/cam4.1454
|View full text |Cite
|
Sign up to set email alerts
|

The importance of greater speed in drug development for advanced malignancies

Abstract: It takes on average 6–12 years to develop new anticancer drugs from discovery to approval. Effective new agents prolong survival. To demonstrate the importance of rapid drug approval, we calculated life‐years potentially saved if selected agents were approved more rapidly. As illustrative examples, we used 27 trials documenting improvements in survival. We multiplied improvement in median survival by numbers of patients dying annually and multiplied this by number of years from drug discovery until approval. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 75 publications
0
33
0
1
Order By: Relevance
“…Such delayed regulatory decisions have real-life consequences: a recent study calculated that accelerating the approval of a single new cancer drug by one year could lead to thousands of life-years gained for patients. However, the impact for any particular drug will depend on the achievable (overall) survival benefit and the number of eligible patients [24]. Moreover, pricing and reimbursement decisions on the national level frequently cause further delays in patients' access to newly approved medicines [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Such delayed regulatory decisions have real-life consequences: a recent study calculated that accelerating the approval of a single new cancer drug by one year could lead to thousands of life-years gained for patients. However, the impact for any particular drug will depend on the achievable (overall) survival benefit and the number of eligible patients [24]. Moreover, pricing and reimbursement decisions on the national level frequently cause further delays in patients' access to newly approved medicines [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Another way of reducing cancer medicine prices is to lower cancer drug development costs. Table outlines some strategies to increase clinical trial efficiency …”
Section: Optimizing Cancer Medicine Researchmentioning
confidence: 99%
“…This clearly implies that a considerable amount of life-years could be saved plausibly through increased efficiency of novel drug development for advanced neoplasms. 88 Further, in the development of different oral agents against cancer, dosing options are random and limited by pills' size. Prasad et al reported that this limited dosing options frequently resulted in large dose adjustments in response to toxicity which might lead to reduced real-world clinical effectiveness of oral anticancer agents resulting in differed outcomes than those achieved in registration trials.…”
Section: Drug Development Duration and Dosing Optionsmentioning
confidence: 99%